2013
DOI: 10.1310/tsr2004-317
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Interval Training in Stroke Rehabilitation

Abstract: After stroke, people with weakness enter a vicious cycle of limited activity and deconditioning that limits functional recovery and exacerbates cardiovascular risk factors. Conventional aerobic exercise improves aerobic capacity, function, and overall cardiometabolic health after stroke. Recently, a new exercise strategy has shown greater effectiveness than conventional aerobic exercise for improving aerobic capacity and other outcomes among healthy adults and people with heart disease. This strategy, called h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 111 publications
0
73
2
2
Order By: Relevance
“…18,19 It is plausible that AEX mode, AEX intensity, AEX volume, stroke chronicity and baseline function would be key factors that influence AEX effect sizes post-stroke. 20,21 For example, neuroplasticity principles indicate that training effectiveness is largely determined by the task-specificity (mode), intensity and repetition (volume) of practice. 21,22 On the other hand, it has been suggested that AEX could improve walking speed and endurance after stroke, regardless of task-specificity (AEX mode).…”
Section: Main Manuscriptmentioning
confidence: 99%
“…18,19 It is plausible that AEX mode, AEX intensity, AEX volume, stroke chronicity and baseline function would be key factors that influence AEX effect sizes post-stroke. 20,21 For example, neuroplasticity principles indicate that training effectiveness is largely determined by the task-specificity (mode), intensity and repetition (volume) of practice. 21,22 On the other hand, it has been suggested that AEX could improve walking speed and endurance after stroke, regardless of task-specificity (AEX mode).…”
Section: Main Manuscriptmentioning
confidence: 99%
“…High-intensity interval training (HIT) is a method that may facilitate the attainment of higher aerobic intensities after stroke [54]. HIT involves concentrated bursts of intense exercise alternated with recovery periods, in varying combinations of burst/recovery duration and intensity.…”
Section: Intensitymentioning
confidence: 99%
“…Approximately 50% of persons with stroke exhibit hemiparesis, or weakness on one side of the body (Go et al 2014;Gresham et al 1979). As a consequence, a majority of persons with stroke have increased fall risk, decreased gait velocity, and exhibit markedly diminished aerobic capacity (Billinger et al 2012;Billinger et al 2014;Boyne et al 2013;Michael et al 2005). This diminished capacity is related to long-term risk for additional cardiac events and recurrent stroke (Mora et al 2007;Tang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent evidence suggests that exercise conducted at higher intensities may be more efficacious than moderate-intensity exercise (Boyne et al 2013;Boyne et al 2015;Burgomaster et al 2005;Hornby et al 2011;Macpherson et al 2011;Rognmo et al 2014). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation